Mites: Ecology, Evolution &Amp; Behaviour 2013
DOI: 10.1007/978-94-007-7164-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Animals as Habitats

Abstract: To most non-biologists, a 'mite' is an almost invisible creature that lives in the carpet and gives you asthma or that burrows in your skin to produce socially unacceptable scabies. Cat owners may curse the ear mites that infest their pets and those who know that ticks are mites may mention Lyme Disease. Such medically important associations between mites and mammals are discussed in most parasitology texts, and mites associated with human diseases are discussed in our Chap. 10 ; therefore, in this chapter we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 220 publications
(273 reference statements)
2
10
0
Order By: Relevance
“…Whether the quantities of bacteria and fungi eaten by feather mites are enough to increase host fitness requires further study. Altogether, our results support previous evidence on the commensalistic–mutualistic role of vane‐dwelling feather mites (Blanco et al., , ; Galván et al., ; Proctor, ; Walter & Proctor, ,b,c). Thus, vane‐dwelling feather mites probably should no longer be considered to be parasites of birds (e.g., Harper, ) but rather commensalists–mutualists.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Whether the quantities of bacteria and fungi eaten by feather mites are enough to increase host fitness requires further study. Altogether, our results support previous evidence on the commensalistic–mutualistic role of vane‐dwelling feather mites (Blanco et al., , ; Galván et al., ; Proctor, ; Walter & Proctor, ,b,c). Thus, vane‐dwelling feather mites probably should no longer be considered to be parasites of birds (e.g., Harper, ) but rather commensalists–mutualists.…”
Section: Discussionsupporting
confidence: 92%
“…If they feed on bird tissues, they are more likely to be classified as parasites (Harper, ; Poulin, ; Thompson, Hillgarth, Leu, & McClure, ), while if they do not, feather mites would more likely be commensals or even mutualists (Blanco, Tella, & Potti, ; Blanco, Tella, Potti, & Baz, ; Galván et al., ). Previous evidence has suggested that feather mites could feed mainly on the uropygial gland oil of birds (Dubinin, ; Proctor, ; Walter & Proctor, ). However, this oil is a nitrogen‐deficient source (Jacob & Ziswiler ; Proctor, ), and previous evidence has shown that feather mites complement their diet with fungi, pollen and algal particles (Blanco et al., ; Dubinin, ; Proctor, ; Walter & Proctor, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they are mainly transmitted vertically from parents to offspring (Doña, Potti et al, ; Jovani, Tella, Sol, & Ventura, ; Proctor, ). Feather mite species are often highly host specific and restricted to a single bird species, usually occurring in specific wing areas and even in particular sections within feathers (Choe & Kim, ; Fernández‐González, Pérez‐Rodríguez, de la Hera, Proctor, & Pérez‐Tris, ; Jovani & Serrano, ; Mironov, ; Proctor, ; Pérez & Atyeo, ; Stefan et al, ; Walter & Proctor, ).…”
Section: Introductionmentioning
confidence: 99%
“…and DNA sequencing confirmed that the sea otter mite is in the Demodex genus. As Demodex mites tend to be monoxenous, 34 this parasite is likely unique to sea otters. The length of sea otter mites (164 µm) is comparable to Demodex sp.…”
Section: Discussionmentioning
confidence: 99%